Metabolic Surgery Effective for Weight Loss and DM Control in Patients With Obesity - Vinall, Maria (MD Conference Express, 2015)
Metabolic surgery (gastric restriction [sleeve gastrectomy and gastric banding], a combination approach using Roux-en-Y gastric banding, and the malabsorption method using a duodenal switch) can effectively and safely reduce weight, achieve diabetes remission, reduce comorbidities, and improve quality of life in obese individuals.